PSYCHOLOGICAL SKILL ASSISTANCE FOR MARRIED COUPLES WHO ARE ALUMNI OF PRE-MARITAL COURSES AT BP4 - PARIAMAN CITY - Arif, M.; Nurhasnah, Nurhasnah; Afrinaldi, Afrinaldi; Mahdi Yusuf, Sri Andayani Binti; Surat, Shahlan (JURNAL AL-IJTIMAIYYAH, 2024)
This paper aims to see how far BP4 Pariaman City has a role in strengthening human psycho-social in the field of social welfare; services for alumni of post-marriage couples need to be followed up with a balanced program. The lack of psycho-social understanding of pre-marital post-marriage course graduates will have great potential to add to the long line of early marriage ages in Pariaman City. The fundamental problem that is most troubling is their ignorance of the responsibilities, rights and obligations of husband and wife in the household. To overcome this solution, the service team identified the problem of spaciousness. It mapped the problem to be treated (treatment) for the subject of service through two stages: family psychology guidance and Islamic family counseling. The first stage is pre-activity in the form of a Focus Discussion Group (FGD) presenting lecturers as participants to provide input for the mentoring action plan to be carried out. The second stage is action activities, including psychological skill assistance in family psychology and group counseling. This activity has generally received appreciation from stakeholders (BP4 Pariaman City management, pre-marital course alumni) because this program has offered various alternatives for their self-development in elaborating their knowledge to be applied in household life. The results of the reflection and evaluation of the program offered by the service conclude that they understand that a sakinah mawaddah wa rahmah household life is not achieved by material wealth but by the ability to accept oneself and have a correct understanding of an Islamic household. They understand that household problems cannot be measured only by logic. However, it includes religious and spiritual matters the human mind cannot reach. Therefore, they understand that household responsibilities are worldly matters and matters of the afterlife, which are related to God.